ANALISIS DAMPAK PEMBELAJARAN MATA KULIAH KEWIRAUSAHAAN DALAM MENUMBUHKAN KEINGINAN BERWIRAUSAHA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS PAMULANG - Jurnal Ekonomi (Journal of Economic Education and Entrepreneurship, 2026)
This study aims to examine the influence of entrepreneurship learning on the formation of entrepreneurial interest in Economics Education students at Pamulang University. The approach used is descriptive qualitative, involving 10 Regular A students who were selected purposively as research subjects. Data collection techniques were carried out through in-depth interviews, observations, and documentation studies. The results of the study indicate that the entrepreneurship learning process can encourage increased student interest in entrepreneurship. This is indicated by the development of an entrepreneurial mindset, increased motivation, and the emergence of creative and innovative business ideas. The application of practical and contextual learning methods also contributes to growing student confidence in starting a business. However, several obstacles such as limited capital and lack of experience remain challenges. Therefore, entrepreneurship learning has a strategic role in fostering students' entrepreneurial spirit.